Testicular salvageability and its predictors among patients with testicular torsion in a resource limited setting: a multicentre longitudinal study - Mohamed Mohamed Abdullahi; Abraha Demoz; Olasinde Anthoney Ayotunde; Kiswezi Ahmed; Molen Selamo F; Muhumuza Joshua; Lule Herman (United Kingdom, 2025)
Introduction: Testicular torsion refers to ischemia of the testicle due to twisting or rotation of the vessels supplying the testes. It is a urologic emergency requiring a high index of clinical suspicion and prompt surgical intervention with management aimed at avoiding testicular loss and resulting infertility. This paper gives an update on the current situation regarding this topic in low-income settings. The aim of this study was to determine testicular salvageability and its predictors amongst patients with testicular torsion at two tertiary African hospitals.
Methods: This was a hospital-based multicentre longitudinal study at two tertiary hospitals in western Uganda. Patients with acute scrotum were enrolled and evaluated for testicular torsion. Those with confirmed testicular torsion underwent surgery and salvageability was reported as the primary outcome. Predictors for testicular salvageability were determined using backward binary logistic regression in SPSS version 22.
Results: During the study period, 232 patients with acute scrotum were enrolled. The mean age was 35.3 (SD = 20.4) years. Forty-one (17.7%) patients had testicular torsion. Only 16 (39.0%) of patients with torsion had viable testes that were salvageable. Orchiectomy was performed on 25 patients (61.0%). At multivariate analysis, a patient who presented after 48 h from the onset of symptoms was 34.833 times more likely to have orchiectomy compared to one who presented within 12 h [AOR = 34.833, (95% CI = 5.020-60.711), P < 0.001].
Conclusion: In this study, the testicular salvage rate was low. The only predictor of salvageability was the time from the onset of symptoms to presentation. All males should be sensitized about the clinical features of testicular torsion to ensure early presentation to increase salvage rates.